Everyday living with osteoarthritis in the global South: A qualitative focus group inquiry in Nigeria - Tolulope Owoyemi; Ibidunni Alonge; Oladapo Adetunji; Emmanuel Ogbu; Adebimpe Ogunbanjo; Simon White; Adewale Adebajo; Christian Mallen; Opeyemi O. Babatunde; Krysia Dziedzic (Osteoarthritis and Cartilage Open)
Objective: Africa contributes significantly to the increasing global prevalence (>37 ​%), unmet need and treatment burden for people with osteoarthritis. Despite this, little research has examined the expressed needs of patients with osteoarthritis (OA) and joint pain in West-Africa. This study aimed to explore lived experiences, expressed needs and current care gaps for people living with osteoarthritis in low-health resource contexts using Nigeria as a case study. Design: Qualitative study using Focus Groups. People aged 45 years and over living with osteoarthritis and joint pain were recruited at local health services or via wide advertisements in the community. Discussions were recorded and transcribed verbatim. Data were analyzed using thematic analysis (inductive approach). Results: Three focus groups were conducted with people living with osteoarthritis (n ​= ​30, age range 45–90 years) across socio-demographic strata. Participants described their experiences of living with osteoarthritis as emotionally, physically, and socio-economically challenging. Four main themes (and 14 sub-themes) were identified. Participants expressed the need for an information and health education campaign and access to appropriate health professionals (especially physiotherapists) for providing support, guidance, and assistance with self-management. Conclusions: The provision of an accessible, and contextually appropriate patient education package, in line with evidence-based recommendations is a critical need for people living with osteoarthritis in Nigeria. This will promote evidence-based care for OA in low-resource settings, empowering patients to self-manage and reducing confusion related to inconsistent advice and mixed messages about cause, healthcare access and OA care.